BANTUAN TUNAI BERSYARAT SEBAGAI PERLINDUNGAN SOSIAL DASAR DI INDONESIA - Oetami Dewi (Politeknik Kesejahteraan Sosial, 2009)
Abstract. The CCT (Conditional Cash Transfer) is being introduced to address shocks caused by fuel price increases with the benefit level set at a level sufficient to compensate the poor for the price increase; however, it is difficult to introduce a higher benefit level for the CCT than was established under the existing unconditional cash transfer. In recent years, conditional cash transfer (CCT) programs have been introduced for a wide array of different purposes. Applied, for instance, to education and childhealth in poor countries, they consist in giving cash to poor parents under the condition that they send their children to school and health visits. These programs have been hailed as being among the most significant innovations in promoting social development in recent years. And through this program we hope the poorest people who are required to be assisted through the poverty program would be released from their poverty circle in the future and in thenext generation.CCTs are quickly becoming central instruments in many countries' poverty reduction agendas. On the economic side, research has shown that the elasticity of poverty to growth is much lower in countries with higher inequality. Growth is seen as necessary but insufficient to reduce poverty. Therefore redistribution must also plays an important role. It is hoped that CCTs' contributions to reducing inequality, combined with economic growth, can provide an equitable foundation for broad-based poverty reduction. On the social side, it is hoped that these longer-term investments will reduce vulnerability in the short-run and in the long run contribute to breaking inter-generational poverty by helping today's children become productive members and full citizens of tomorrow 'ssociety.CCTs feed into the broader debate on social inclusion on several levels as they often lead to changes in accountability relationships between central governments, local governments, service providers and beneficiaries. among others. On the level of national social policy CCTs are gaining popularity as instruments for reaching excluded groups, notably the extreme poor living outside the reach of social protection programs tied to formal sector employment. Many still argue that despite efforts at program coordination, however CCTs must be adequately inserted within a broader institutional reform of social and economic programs that would bring about effective inclusion and poverty reduction. On a local level, some CCT programs have been criticized for using mechanisms that run counter to the social inclusion goals with respect of local governments and communities.Keyword : conditional cash transfer programme, poverty reduction, human capital.